2019
DOI: 10.3389/fped.2019.00156
|View full text |Cite
|
Sign up to set email alerts
|

Psychometrics of the Functional Oral Intake Scale for Infants

Abstract: This study aimed to investigate the reliability and validity of the Functional Oral Intake Scale (FOIS) for infants. Infants (age, <1 year) who underwent a videofluoroscopic swallowing study (VFSS) were included in this retrospective study. Their nutrition records at the time of the VFSS were separately evaluated by two raters using the five-point FOIS for infants. Categorical swallowing and aspiration impairment scale data were also obtained from the VFSS. The inter-rater reliability of the FOIS for infants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…We used the 6‐point graded p‐FOIS which had excellent interrater reliability and validity, similar to previous studies in adults and paediatric cohorts and enabling tracking of functional abilities using a single measure across all time points. 14 , 19 , 20 Of note, we evaluated the p‐FOIS in children aged 0 to 16 years in the validation process, reflecting the full age range of SMA assessed in most paediatric settings.…”
Section: Discussionmentioning
confidence: 99%
“…We used the 6‐point graded p‐FOIS which had excellent interrater reliability and validity, similar to previous studies in adults and paediatric cohorts and enabling tracking of functional abilities using a single measure across all time points. 14 , 19 , 20 Of note, we evaluated the p‐FOIS in children aged 0 to 16 years in the validation process, reflecting the full age range of SMA assessed in most paediatric settings.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous efforts to adapt the FOIS 13 for use with children have been made, but none were suited to assessing outcomes in a population with paediatric feeding disorders irrespective of the child's age, underlying aetiology, or care setting. [16][17][18][19][20] This study used systematic compilation of expert opinions to develop collective agreement on level descriptor wording for a 6-point ordinal scale measuring functional oral intake in children. To reduce confusion, given the number of previously reported paediatric FOIS versions, the study team proposes calling this scale the Children's Eating and Drinking Activity Scale (CEDAS).…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is no validated tool for assessing dysphagia in children. Still, the FOIS for adults has been modified and is widely used for infants 9,31 based on recommendations of the European Society of Pediatric Gastroenterology, Hepatology, and Nutrition Committee on Nutrition 30 . Additionally, clinical practice has shown that the FOIS is appropriate for younger children 12 .…”
Section: Discussionmentioning
confidence: 99%